2021
DOI: 10.3389/fped.2021.633532
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Clinical Analysis of Seven Neonates With Prader-Willi Syndrome and Review of the Literature

Abstract: Objective: The clinical symptoms of neonatal Prader-Willi syndrome (PWS) are not typical and are easy to miss. The aim of the study was to investigate the clinical features and genetic characteristics of seven cases of neonatal PWS from northern China, and to improve the understanding of PWS in neonates.Methods: We retrospectively analyzed seven infants diagnosed by methylation specific multiplex ligation probe amplification technology (MS-MLPA) in the Neonatology Unit of Shengjing Hospital of China Medical Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Prader Willi Syndrome (PWS) is one of the most common causes of genetic obesity, with an incidence rate of approximately 1 in 10,000 to 1 in 25,000 live births. The condition was first described by Swiss researchers, Andrea Prader, Heinrich Willi, and Alexis Labhart, in 1956 as children with feeding difficulties, poor muscle tone, underdeveloped sex organs, short stature, small hands and feet, and some cognitive and behavioral impairments [ 1 , 2 ]. Genetic testing can diagnose the condition which is caused by the absence of expression of imprinted genes in the paternally derived region of chromosome 15q11-q13, also known as the Prader Willi critical region [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prader Willi Syndrome (PWS) is one of the most common causes of genetic obesity, with an incidence rate of approximately 1 in 10,000 to 1 in 25,000 live births. The condition was first described by Swiss researchers, Andrea Prader, Heinrich Willi, and Alexis Labhart, in 1956 as children with feeding difficulties, poor muscle tone, underdeveloped sex organs, short stature, small hands and feet, and some cognitive and behavioral impairments [ 1 , 2 ]. Genetic testing can diagnose the condition which is caused by the absence of expression of imprinted genes in the paternally derived region of chromosome 15q11-q13, also known as the Prader Willi critical region [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prader-Willi syndrome (PWS) is a typical example of imprinting inheritance [ 25 ]. Maternal UPD on chromosome 15 can lead to PWS, and the main intrauterine manifestations of PWS are reduced fetal movement and FGR [ 26 ]. This study confirmed that one fetus had maternal UPD on chromosome 15 (PWS), and ultrasonographic findings of this fetus revealed FGR and polyhydramnios.…”
Section: Discussionmentioning
confidence: 99%
“…While we initially suspected these findings were the result of Down syndrome combined with an acute illness, a chromosomal microarray was ordered and returned with findings suggestive of a second diagnosis that was later confirmed by methylation analysis to be Prader-Willi syndrome. This provided an explanation for his overwhelming hypotonia [13].…”
Section: Beyond the Classic Phenotypementioning
confidence: 91%